Flow Cytometry Detection of Sperm DNA Fragmentation and Apoptotic Markers in the Semen of Infertile Males - Omran, Huda Mossa; Bakhiet, Moiz; Ehemann, Volker (International Journal of Reproductive Medicine, 2021)
The effect of sperm molecular defects on fertilization and pregnancy outcome after assisted reproductive therapy (ART) is widely documented by both research and clinical societies. Sperm DNA fragmentation and abnormal chromatin condensation represent critical causes of male infertility. Advanced androgenic techniques for accurately identifying molecular defects help in selecting an appropriate treatment strategy. Additionally, specific markers of apoptosis are increasingly important in predicting male infertility. The ability of flow cytometry to estimate the quantity of sperm with DNA fragmentation or damage and multifactor measurements in immotile sperm have made this developed technique essential in fertility centers. The study is aimed at assessing the level of DNA fragmentation and apoptosis by measuring flow cytometry using new techniques. Flow cytometry analysis revealed a varying degree of DNA damage. It was able to quantify the degree of impairment even in samples with minimal DNA fragmentation. DNA damage was observed even in samples that were considered normal with a routine semen analysis. Flow cytometry was sensitive to changes in sperm apoptosis. Elevated p53 activity levels were associated with high DNA fragmentation. Meanwhile, B-cell lymphoma 2 (Bcl-2) activities showed a different pattern. In conclusion, flow cytometry for sperm DNA fragmentation and markers of apoptosis can be a valuable tool in assisted reproductive centers.